Synthesis and Characterization of Bisthienylethene‐Porphyrin Photoswitchable Copolymers - Huo, Zhaohui; Badets, Vasilica; Ibrahim, Helen; Goldmann, Michel; Xu, Hualong; Yi, Tao; Boudon, Corinne; Ruhlmann, Laurent (European journal of organic chemistry, 2021)
The bisthienylethene (BTE) class is one of the most intensely studied type of photochromatic dye which attract great attention from researchers seeking to exploit light responsive switches in an extensive diversity of fields. BTE is the subject of many avenues of research. We report here the synthesis of a new diarylethene‐porphyrin photoswitchable copolymer via the electropolymerization of zinc octaethyl porphyrin and pyridine substituted diarylethene. The electropolymerization was monitored by electrochemical quartz crystal microbalance (EQCM). The copolymer was characterized by electrochemistry, UV‐Vis spectroscopy, X‐ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM). The incorporated diarylethene maintains its reversible photochromism upon the UV‐Vis radiation with multiple cycles of ring‐opening and closing. Attention is focused on the ways the polymer environment affects BTE photochromism. The synthesis of a new diarylethene‐porphyrin photoswitchable copolymer through the electropolymerization of zinc octaethyl porphyrin and pyridine substituted diarylethene is reported. The incorporated diarylethene maintains its reversible photochromism upon exposure to UV‐Vis radiation with multiple cycles of ring opening and closing.